solve the pair  linear equations

(a+b)x+(a-b)y=asquare+bsquare

(a-b)x+(a+b)y=asquare+bsquare

Asked by harmanpreetsinghdhindsa955 | 2nd Oct, 2020, 11:33: AM

Expert Answer:

(a+b)x + (a-b)y = a2 + b2 ... (i)
(a-b)x + (a+b)y = a2 + b2 ... (ii)
Multiplying (i) and (ii) by (a+b) and (a-b) respectively, we get
(a + b)2x + (a2 - b2)y = a3 + b3 + a2b + ab2 ... (iii)
(a - b)2x + (a2 - b2)y = a3 + b3 - a2b + ab2 ... (iv)
Subtracting (iv) from (iii), we get
(a2 + 2ab + b2 - a2 + 2ab - b2)x = 2a2
4abx = 2a2b
x = a/2
Put the value of x in either of the two equations and get the value of y

Answered by Renu Varma | 2nd Oct, 2020, 08:21: PM